Advantages and disadvantages of using the Internet of Things in accounting - M.H. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Since the beginning of the existence of the Internet, devices have been connected to it, and in the modern world everything has become more perfect and convenient. Also, the devices themselves have become more compact and accessible to ordinary people, so the Internet of Things or connected devices can be considered the driving force of Industry 4.0, which is also called digital, that is, artificial intelligence can perform certain operations without human assistance. New opportunities are opening up for companies and enterprises, they can significantly save their costs, both time and money, which will help to effectively perform work for the modern business sphere. An employee of the accounting service must be ready for new challenges, because the accounting documentation system is changing. Therefore, every modern accountant must be flexible to digital changes, acquire new knowledge, abilities and skills that are needed in the modern world. But not all new changes are immediately ideal, so there are a number of advantages and disadvantages of the Internet of Things in accounting. The advantage of the Internet of Things in accounting can be considered automation. Devices connected to the Internet collect the necessary data for the employee of the accounting service and, as a result, automatically enter financial data into the accounting system, this advantage allows for quick processing of information, and also reduces the risk of human errors in entering accounting data. But there are also disadvantages of using the Internet of Things in accounting. The main drawback is security and data protection. Ultimately, devices that are not sufficiently secured can be vulnerable to cyber attacks, which can lead to the leakage of financial and other important data stored by businesses. In order to succeed in the implementation of digital changes in accounting, it is necessary to analyze in detail the advantages and disadvantages of new technologies.